Analysis of Passenger Commuter Train Services Surabaya – Sidoarjo - Hermanto Dwiatmoko; Nabila Nabila; Sri Wiwoho Mudjanarko; M Ikhsan Setiawan (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2020)
This study aims to determine the service level of the Surabaya - Sidoarjo commuter train which is part of the transportation service in the Gerbang Kertasusila area. Surabaya is the second-largest city in Indonesia as the center of regional government for East Java and is the center of activity for all sectors in the region. The high population density and the high value of land in Surabaya have resulted in people choosing to live in Gerbang Kertasusila areas, namely Gresik, Bangkalan, Kertosono, Surabaya, Sidoarjo, and Lamongan (Gerbang Kertasusila). This resulted in the high movement of commuters from the buffer area for activities in downtown Surabaya. In this study, the analysis was carried out regarding the Minister of Transportation Regulation number 63 the year 2019 concerning Minimum Service Standards for Passenger Train Transportation. The research methodology used is Importance Performance Analysis by distributing questionnaires to commuter train users across Surabaya - Sidoarjo to find out people's opinions about train transportation services operated by PT. Kereta Api Indonesia. The results of the study can identify the level of service at the station and on the train, both those that are a priority to be improved and those that must be maintained.